Sb-NCM positive electrode material and preparation method thereof
By doping Sb5+ in the high-nickel layered oxide positive electrode material, its instability problem under high voltage, fast charging and discharge and low temperature conditions is solved, and the cycle life, safety and rate performance of lithium batteries are significantly improved. Suitable for high power applications.
Patent Information
- Application Number
- CN202411782752.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The performance of high-nickel layered oxide positive electrode materials under high voltage cycle, fast charging and discharge and low temperature conditions is unstable, resulting in structural phase change, oxygen release, electrolyte side reactions and safety problems, limiting the commercial application of lithium batteries.
采用Sb-NCM正极材料的化学式为Li[NixMnyCozSbt]O2,通过镍盐、锰盐、钴盐与锑源的摩尔比调整和超声处理,结合多段煅烧工艺,掺杂Sb5+占据Ni2+基底晶格点位,优化材料结构和界面稳定性。
It significantly improves the stability of the material under high voltage, fast charging and discharging and low temperature conditions, extends the cycle life, enhances the safety and rate performance of the battery, and is suitable for high-power applications.
Smart Images

Figure CN119297268A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a Sb-NCM positive electrode material and a preparation method thereof. Background Art
[0002] With the global energy structural transformation and the increasing environmental awareness, the market demand for lithium-ion batteries is increasing. In recent years, lithium battery technology has made significant progress in energy density, fast charging technology, solid-state battery technology and battery management system.
[0003] Due to the increasing market demand for high-performance and highly competitive lithium batteries, the research and development breakthroughs of positive electrode materials, as one of the core components of lithium batteries, have attracted much attention. In recent years, high-nickel layered oxides have attracted much attention due to their high energy density, but their performance instability under high-voltage cycling, rapid charging and discharging, and low-temperature conditions has significantly limited their potential for commercial application. High-nickel materials are prone to irreversible structural phase changes under high pressure, and the oxygen release problem further accelerates material degradation, resulting in electrolyte side reactions and SEI film problems under high voltage and even a series of safety issues, resulting in shorter cycle performance and significantly reduced safety. At the same time, at low temperatures, lithium ions are hindered from migrating due to increased interfacial impedance, resulting in a decrease in charge and discharge efficiency and poor rate performance. Therefore, it is very necessary to provide a Sb-NCM positive electrode material and a preparation method thereof to solve the structural instability of high-nickel layered oxide positive electrode materials. Summary of the invention
[0004] In view of this, the present invention provides a Sb-NCM positive electrode material and a preparation method thereof to solve the problem that the existing high-nickel layered oxide positive electrode material has poor stability under high voltage cycling and rapid charge and discharge conditions.
[0005] In order to achieve the above object, the present invention adopts the following technical solution: A Sb-NCM positive electrode material, the chemical formula of the Sb-NCM positive electrode material is Li[Ni x Mn y Co z Sb t ]O2, where x≥0.8, y≤0.1, z≤0.1, t≤0.1 and y+z+t≤0.2.
[0006] Preferably, the chemical formula of the Sb-NCM positive electrode material is Li[Ni 0.895 Mn 0.05 Co 0.05 Sb 0.005 ]O2.
[0007] Another object of the present invention is to provide a method for preparing a Sb-NCM positive electrode material, comprising the following steps: 1) dissolving nickel salt, manganese salt and cobalt salt to obtain a mixed solution, mixing the mixed solution with an alkaline solution to react and obtain a hydroxide precipitate; 2) Preliminarily calcining the hydroxide precipitate obtained in step 1) to obtain an intermediate product; 3) The intermediate product is mixed with a lithium source and an antimony source, and calcined again to obtain a Sb-NCM positive electrode material; The molar ratio of nickel salt, manganese salt, cobalt salt and antimony source is x+t:y:z:t.
[0008] Preferably, the reaction temperature in step 1) is 35-40° C., the reaction time is 0.5-2 h, and the reaction pH is 8.5-9.5.
[0009] Preferably, the nickel salt includes one or more of nickel nitrate, nickel chloride and nickel sulfate; The manganese salt includes one or more of manganese nitrate, manganese chloride and manganese sulfate; The cobalt salt includes one or more of cobalt nitrate, cobalt chloride and cobalt sulfate.
[0010] Preferably, the reaction in step 1) is carried out under ultrasonic conditions, and the frequency of the ultrasound is 20-100 kHz.
[0011] Preferably, the temperature of the preliminary calcination in step 2) is 300-500° C., and the time of the preliminary calcination is 60-120 min.
[0012] Preferably, the re-calcination in step 3) comprises a first stage calcination and a second stage calcination performed sequentially; The calcination temperature of the first stage is 450~570℃, and the calcination time is 200~300min; The calcination temperature of the second stage is 750~870℃, and the calcination time is 1000~1400min; The calcination atmospheres of the first stage calcination and the second stage calcination are independently oxygen atmospheres.
[0013] Preferably, the lithium source in step 3) includes one or more of lithium carbonate, lithium hydroxide, lithium sulfate and lithium nitrate; The antimony source includes antimony pentoxide and / or sodium antimonate.
[0014] The present invention uses Sb without sacrificing energy density. 5+ For Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2 (NCM90) positive electrode material is doped, where Sb 5+ Take Ni 2+The substrate lattice sites optimize the performance of the positive electrode material under high voltage, rapid charging and discharging, and low temperature conditions, significantly improve the degradation problem, and enhance the cycle life, rate performance, and safety.
[0015] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects: 1. Improve structural stability and reduce phase change High-nickel materials are prone to irreversible phase changes (such as from layered phase to rock salt phase or spinel phase) under high voltage, which leads to obstruction of lithium ion diffusion channels and rapid capacity decay. 5+ The doping of occupies some nickel sites, reduces the proportion of nickel in high oxidation states, stabilizes the lattice structure, and thus significantly inhibits the phase change of the material. The structure of the material remains stable under high pressure, reducing the occurrence of irreversible phase change, thereby extending the cycle life of the battery.
[0016] 2. Inhibit oxygen release and enhance battery safety Ni in high nickel materials 4+ At high voltages, it is easy to cause oxygen release, which in turn reacts with the electrolyte, causing battery degradation and possibly thermal runaway. Sb 5+ The doping of can reduce oxidation stress and the tendency of oxygen release, thereby preventing excessive side reactions inside the battery. The thermal stability of the battery is enhanced, reducing battery failures and safety hazards caused by oxygen release, and improving the safety of the battery under high voltage and high temperature conditions.
[0017] 3. Reduce electrolyte side reactions and improve interface stability In high-voltage cycles, high-nickel materials are prone to side reactions with the electrolyte, resulting in excessive generation of thick and unstable solid electrolyte interfaces (SEI films), which increase impedance and reduce battery performance. 5+ It can form a more stable chemical environment on the surface of the material, reduce the reaction with the electrolyte, and thus optimize the electrode-electrolyte interface. The interface stability is improved, the growth of the SEI film is inhibited, and the internal resistance of the battery is reduced, thereby improving the long-cycle performance and efficiency of the battery.
[0018] 4. Improve low temperature performance and increase charging and discharging efficiency at low temperatures High nickel materials exhibit poor electrochemical performance at low temperatures, which is mainly reflected in the significant decrease in lithium ion migration rate and reduced battery capacity. 5+ The doping stabilizes the lattice structure, optimizes the lithium ion channel, reduces the impedance under low temperature conditions, and enables lithium ions to migrate effectively under low temperature conditions. Under low temperature conditions, the battery's charge and discharge performance is significantly improved, and the capacity decay rate is slowed down, making it particularly suitable for use in cold environments.
[0019] 5. Improved rate performance, suitable for high power applications High nickel materials are prone to lithium ion diffusion blockage or reduced electron conduction efficiency during high rate charge and discharge. 5+ Doping can reduce the structural collapse of the material during rapid charge and discharge, increase the diffusion rate of lithium ions, and reduce the impedance under high current conditions. The battery's capacity retention rate at high-rate charge and discharge is improved, and it can withstand the needs of fast charging and high-power output, making it very suitable for high-power devices such as electric vehicles.
[0020] 6. Extend cycle life and reduce capacity attenuation High nickel materials are prone to structural stress accumulation and microcracks during long-term cyclic use, resulting in rapid battery capacity decay. 5+ Finally, by optimizing the mechanical stability of the material, the stress concentration and microcrack formation during the charge and discharge process were reduced, and the structural integrity between particles was enhanced. The material showed better structural stability and slowed capacity decay in long-term cycle use, significantly extending the service life of the battery.
[0021] The present invention adopts Sb 5+ Doping technology effectively solves the shortcomings of high-nickel cathode materials in terms of structural stability, oxygen release, interface reaction, low temperature performance, rate performance, and cycle life. By enhancing the physical and chemical stability of the material, the overall performance of the battery is significantly improved, especially under charging stagnation, high voltage, high rate and low temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0023] Figure 1 XRD characterization diagrams of the positive electrode materials prepared in Examples 1 to 3 of the present invention and the NCM90 positive electrode material; Figure 2 The SEM characterization images of the positive electrode materials prepared by NCM90 and Example 1 are as follows: Figure 2 The a in corresponds to NCM90, Figure 2 b in the embodiment corresponds to Example 1; Figure 3 The cyclic voltammetry test results of the battery prepared by the positive electrode material obtained in Example 1 of the present invention; Figure 4 The long cycle performance test results of the battery prepared with the positive electrode material obtained in Example 1 of the present invention; Figure 5 This is an EIS test chart of a battery prepared with the positive electrode material obtained in Example 1 of the present invention after standing for one day. DETAILED DESCRIPTION
[0024] The present invention provides a Sb-NCM positive electrode material, wherein the chemical formula of the Sb-NCM positive electrode material is Li[Ni x Mn y Co z Sb t ]O2, wherein x≥0.8, y≤0.1, z≤0.1, t≤0.1 and y+z+t≤0.2, x can specifically be 0.85, 0.86, 0.88, 0.895, 0.9, 0.92, 0.95, y can specifically be 0.01, 0.02, 0.05, 0.06, 0.08, z can specifically be 0.01, 0.02, 0.05, 0.06, 0.08, and t can specifically be 0.01, 0.02, 0.05, 0.06, 0.08.
[0025] In the present invention, the chemical formula of the Sb-NCM positive electrode material is Li[Ni 0.895 Mn 0.05 Co 0.05 Sb 0.005 ]O2.
[0026] The present invention also provides a method for preparing a Sb-NCM positive electrode material, comprising the following steps: 1) dissolving nickel salt, manganese salt and cobalt salt to obtain a mixed solution, mixing the mixed solution with an alkaline solution to react and obtain a hydroxide precipitate; 2) Preliminarily calcining the hydroxide precipitate obtained in step 1) to obtain an intermediate product; 3) The intermediate product is mixed with a lithium source and an antimony source, and calcined again to obtain a Sb-NCM positive electrode material.
[0027] In the present invention, the molar ratio of nickel salt, manganese salt, cobalt salt and antimony source in the preparation method is x+t:y:z:t; after adding Sb, Sb 5+ Will take you 2+ The substrate lattice site is similar to the Ni 2+ Make a replacement.
[0028] In the present invention, the reaction temperature in step 1) is 35-40°C, specifically 36°C, 37°C, 38°C, 39°C; the reaction time is 0.5-2h, specifically 0.8h, 1h, 1.2h, 1.5h, 1.8h; the reaction pH is 8.5-9.5, specifically 8.6, 8.8, 9, 9.2, 9.4.
[0029] In the present invention, the alkaline solution includes one or more of potassium hydroxide solution, sodium hydroxide solution and ammonia water.
[0030] In the present invention, the nickel salt includes one or more of nickel nitrate, nickel chloride and nickel sulfate; the manganese salt includes one or more of manganese nitrate, manganese chloride and manganese sulfate; the cobalt salt includes one or more of nickel nitrate, nickel chloride and cobalt sulfate.
[0031] In the present invention, the nickel salt, manganese salt and cobalt salt also include hydrates corresponding to the listed salts.
[0032] In the present invention, the reaction in step 1) is carried out under ultrasonic conditions, and the frequency of the ultrasound is 20-100 kHz, specifically 40 kHz, 50 kHz, 60 kHz, and 80 kHz.
[0033] In the present invention, ultrasonic treatment can promote the material preparation process of the present invention through its unique cavitation, stirring and coagulation effects. It can not only improve the dispersibility and uniformity of the material, but also optimize the structural particle morphology, size distribution and electrochemical properties of the material, thereby realizing a more stable and efficient controllable material preparation process, and significantly improving the comprehensive performance of the battery, including cycle life, rate performance and stability.
[0034] In the present invention, the temperature of the preliminary calcination in step 2) is 300-500°C, specifically 320°C, 350°C, 380°C, 400°C, 420°C, 450°C, 480°C; the time of the preliminary calcination is 60-120min, specifically 70min, 80min, 90min, 100min, 110min.
[0035] In the present invention, the re-calcination in step 3) includes a first stage calcination and a second stage calcination performed sequentially.
[0036] In the present invention, the calcination temperature of the first stage calcination is 450-570°C, specifically 460°C, 480°C, 500°C, 520°C, 540°C, 550°C, 560°C; the calcination time is 200-300min, specifically 220min, 240min, 250min, 260min, 280min.
[0037] In the present invention, the calcination temperature of the second stage calcination is 750-870°C, specifically 760°C, 780°C, 800°C, 820°C, 840°C, 850°C, 860°C; the calcination time is 1000-1400min, specifically 1050min, 1100min, 1150min, 1200min, 1250min, 1300min, 1350min.
[0038] In the present invention, the calcination atmospheres of the first stage calcination and the second stage calcination are independently oxygen atmospheres.
[0039] In the present invention, the heating rates of the first and second calcinations are independently preferably 3-5°C / min, specifically 3.2°C / min, 3.4°C / min, 3.5°C / min, 3.6°C / min, 3.8°C / min, 4°C / min, 4.2°C / min, 4.4°C / min, 4.5°C / min, 4.6°C / min, and 4.8°C / min.
[0040] In the present invention, after the first stage calcination is completed, the temperature is preferably directly raised to the second stage calcination temperature.
[0041] In the present invention, the lithium source in step 3) includes one or more of lithium carbonate, lithium hydroxide, lithium sulfate and lithium nitrate; The antimony source includes antimony pentoxide and / or sodium antimonate.
[0042] In the present invention, the lithium source is lithium carbonate, and the calcination temperature of the first stage calcination is preferably 450-470°C, specifically 455°C, 460°C, and 465°C; the calcination time is preferably 200-300min, specifically 220min, 250min, and 280min; the calcination temperature of the second stage calcination is preferably 750-870°C, specifically 755°C, 760°C, 780°C, 800°C, 820°C, 850°C, and 860°C; the calcination time is preferably 1232min.
[0043] In the present invention, the lithium source is lithium hydroxide, and the calcination temperature of the first stage calcination is preferably 450-470°C, specifically 455°C, 460°C, and 465°C; the calcination time is preferably 200-300min, specifically 220min, 250min, and 280min; the calcination temperature of the second stage calcination is preferably 750-770°C, specifically 755°C, 760°C, and 765°C; the calcination time is preferably 1000-1400min, specifically 1050min, 1100min, 1150min, 1200min, 1250min, 1300min, and 1350min.
[0044] In the present invention, the mixing in step 3) is preferably grinding mixing, and during the grinding process, Sb 5+ Take Ni 2+ The substrate lattice site is similar to the Ni 2+ Make a replacement.
[0045] In the present invention, the mixing time is preferably 20 to 25 hours, specifically 21 hours, 22 hours, 23 hours, or 24 hours.
[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] Example 1 Li[Ni 0.895 Mn 0.05 Co 0.05 Sb 0.005 Preparation of O2 cathode materials Nickel nitrate hexahydrate, manganese nitrate tetrahydrate and cobalt nitrate hexahydrate were weighed in a molar ratio of 0.9:0.05:0.05 and dissolved in deionized water. Then, NaOH solution was used as a precipitant, and NaOH solution (pH value = 12) was quickly added to the mixed solution at one time by positive addition method, and the pH value of the mixed solution was adjusted to 9.5, and the temperature was maintained at 40°C. When the reaction began to generate precipitation, the mouth of the reaction beaker was covered with plastic wrap, and an ultrasonic instrument with a frequency of 50kHz was used to irradiate the reaction for 1 hour to generate metal hydroxide (Ni(OH)2, Mn(OH)2, Co(OH)3) precipitation.
[0048] The metal hydroxide precipitate is obtained by centrifugal separation and then dried at 80° C. After drying, the metal hydroxide precipitate is calcined at 400° C. for 100 min to obtain a metal oxide.
[0049] The metal oxides were mixed with lithium hydroxide and antimony pentoxide by ball milling in a planetary ball mill (the molar ratio of Li, Ni, Mn, Co and Sb in the metal oxides, lithium hydroxide and antimony pentoxide was 1:0.9:0.05:0.05:0.005), the grinding balls were 15 mm, 10 mm and 5 mm respectively, the configuration mass ratio was 30% large balls, 30% medium balls and 40% small balls, the ball-to-material ratio was 10:1, and the grinding was carried out for 24 hours. The lithiation treatment was completed.
[0050] The mixture after lithium treatment was placed in an oxygen atmosphere and heated to 450°C at a heating rate of 4°C / min and kept at this temperature for 240 min; then the mixture was heated to 750°C at a heating rate of 4°C / min and kept at this temperature for 1232 min to obtain the Sb-NCM positive electrode material (Li[Ni 0.895 Mn 0.05 Co 0.05 Sb 0.005 ]O2).
[0051] Example 2 Li[Ni 0.893 Mn 0.05 Co 0.05 Sb 0.007 Preparation of O2 cathode materials Nickel nitrate hexahydrate, manganese nitrate tetrahydrate and cobalt nitrate hexahydrate were weighed in a molar ratio of 0.9:0.05:0.05 and dissolved in deionized water. Then, NaOH solution was used as a precipitant, and NaOH solution (pH value = 12) was quickly added to the mixed solution at one time by positive addition method, and the pH value of the mixed solution was adjusted to 8.5, and the temperature was maintained at 35°C. When the reaction began to generate precipitation, the mouth of the reaction beaker was covered with plastic wrap, and an ultrasonic instrument with a frequency of 80kHz was used to irradiate the reaction for 2 hours to generate metal hydroxide (Ni(OH)2, Mn(OH)2, Co(OH)3) precipitation.
[0052] The metal hydroxide precipitate is obtained by centrifugal separation and then dried at 80° C. After drying, the metal hydroxide precipitate is calcined at 300° C. for 120 min to obtain a metal oxide.
[0053] The metal oxides were ball-milled with lithium hydroxide and antimony pentoxide using a planetary ball mill (the molar ratio of Li, Ni, Mn, Co and Sb contained in the metal oxides, lithium hydroxide and antimony pentoxide was 1:0.9:0.05:0.05:0.007), the grinding balls were 15 mm, 10 mm and 5 mm respectively, the configuration mass ratio was 30% large balls, 30% medium balls and 40% small balls, the ball-to-material ratio was 10:1, and the grinding lasted for 24 hours. The lithiation treatment was completed.
[0054] The mixture after lithium treatment was placed in an oxygen atmosphere and heated to 470°C at a heating rate of 4°C / min and kept warm for 200 min; then the temperature was continued to be raised to 770°C at a heating rate of 4°C / min and kept warm for 1000 min to obtain Sb-NCM positive electrode material (Li[Ni 0.893 Mn 0.05 Co 0.05 Sb 0.007 ]O2).
[0055] Example 3 Li[Ni 0.897 Mn 0.05 Co 0.05 Sb 0.003 Preparation of O2 cathode materials Nickel nitrate hexahydrate, manganese nitrate tetrahydrate and cobalt nitrate hexahydrate were weighed in a molar ratio of 0.9:0.05:0.05 and dissolved in deionized water. Then, NaOH solution was used as a precipitant, and NaOH solution (pH value = 12) was quickly added to the mixed solution at one time by positive addition method, and the pH value of the mixed solution was adjusted to 9. The temperature was maintained at 38°C. When the reaction began to generate precipitation, the mouth of the reaction beaker was covered with plastic wrap, and an ultrasonic instrument with a frequency of 30kHz was used to irradiate the reaction for 1.5 hours to generate metal hydroxide (Ni(OH)2, Mn(OH)2, Co(OH)3) precipitation.
[0056] The metal hydroxide precipitate is obtained by centrifugal separation and then dried at 80° C. After drying, the metal hydroxide precipitate is calcined at 500° C. for 60 min to obtain a metal oxide.
[0057] The metal oxides were mixed with lithium carbonate and antimony pentoxide by ball milling in a planetary ball mill (the molar ratio of Li, Ni, Mn, Co and Sb in the metal oxides, lithium hydroxide and antimony pentoxide was 1:0.9:0.05:0.05:0.003), the grinding balls were 15mm, 10mm and 5mm respectively, the configuration weight ratio was 30% large balls, 30% medium balls and 40% small balls, the ball-to-material ratio was 10:1, and the grinding lasted for 24 hours. The lithiation treatment was completed.
[0058] The lithium-treated mixture was placed in an oxygen atmosphere and heated to 460°C at a heating rate of 4°C / min and kept at this temperature for 240 min; then the temperature was further heated to 770°C at a heating rate of 4°C / min and kept at this temperature for 1232 min to obtain the Sb-NCM positive electrode material (Li[Ni 0.897 Mn 0.05 Co 0.05 Sb 0.003 ]O2).
[0059] Comparative Example 1 The difference between this comparative example and Example 1 is that no antimony pentoxide is added, and Li[Ni 0.90 Co 0.05 Mn 0.05 ]O2 positive electrode material. Note as NCM90.
[0060] Experimental Example 1 XRD characterization was performed on the positive electrode materials prepared in Examples 1 to 3 and the NCM90 positive electrode material. The characterization results are as follows: Figure 1As shown, through Figure 1 It can be seen that the black curve in the stacking diagram represents the XRD spectrum of the undoped NCM90 cathode particles. The above three curves are all different Sb 5+ The XRD patterns of the doped Sb-NCM positive electrode particles (corresponding to Examples 1 to 3, respectively) were refined and analyzed by JADE, and it can be concluded that the material described in the present invention can be successfully prepared at different doping amounts, different sintering temperatures, and different values of each parameter.
[0061] The crystal structure parameters of the positive electrode materials of NCM90 and Example 1 determined according to the XRD results obtained by JADE treatment are shown in Table 1.
[0062] Table 1 Crystal structure parameters
[0063] From Table 1, we can see that the a-axis length, c-axis length, unit cell volume, Ni 2+ The proportion of Li sites occupied by ions is very close to the parameters of NCM90, indicating that the crystal structure of Sb-NCM modified by antimony doping has not changed much from that of the reference standard NCM90. 5+ The ions did not destroy the original crystal structure.
[0064] The SEM characterization pictures of the positive electrode materials of NCM90 and Example 1 are as follows Figure 2 As shown, Figure 2 The a in corresponds to NCM90, Figure 2 b in the embodiment corresponds to Example 1. Figure 2 It can be seen that in the NCM90 sample without antimony doping, the particle surface is relatively rough, which will lead to structural instability of the electrode material during the charge and discharge process. The high nickel content in the high-nickel layered material will cause it to be prone to structural changes and interface cracks during the cycle, and this surface roughness may further aggravate this instability. In contrast, the particle surface of the Sb-NCM positive electrode material prepared in Example 1 is denser and smoother, showing the role of antimony doping in improving the surface morphology of the particles. The smoother surface reduces the fluctuation of the contact area between the particles, thereby effectively alleviating the problem of particle structure damage and interface impedance during the charge and discharge cycle.
[0065] Experimental Example 2 A 2032-type button cell was prepared using the positive electrode material prepared in Example 1. The preparation method was as follows: first, the Sb-NCM positive electrode material obtained in Example 1 was uniformly ground and mixed with a conductive agent (carbon black (Super P)) and a binder (PVDF) (the mass ratio of the positive electrode material, the conductive agent and the binder was 90:5.5:4.5); then, a solvent NMP (N-methylpyrrolidone) was added to the ground and mixed powder and fully mixed to a thick slurry; the slurry was coated on a current collector at 4.5 mg per square centimeter, and then placed in a vacuum drying oven and dried at 110°C for 5 hours (the cathode can be removed after thorough drying) to obtain a cathode; battery assembly: 1.2 MLiPF6 (lithium hexafluorophosphate) was dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (EC:EMC = 3:7 (vol%)), and 2 wt.% of vinylene carbonate (VC) was added as an electrolyte additive, and the above mixed solution was the electrolyte. A metal lithium sheet (Honjo Metal Co., Ltd., Japan, purity>99.9%, thickness: 200µm) was used as the anode, the above material was used as the cathode, three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP, Celgard 2320, thickness: 20µm) were used as the separator, and 200µL of the above electrolyte was used to assemble 2032 coin-type batteries in a glove box. Cyclic voltammetry (CV) (CV voltage range of 2.7V~4.3V, scan rate of 1e-4, scan 10 segments) was used for testing. The results of cyclic voltammetry test of Example 1 are as follows: Figure 3 As shown, through Figure 3 Obvious redox peaks can be observed, indicating that the lithium ion insertion / deinsertion process of the material has good reversibility. The optimization effect of antimony doping on NCM90 is reflected in the stability of its redox peak position, indicating that the antimony-doped material has less irreversible phase change in high-voltage cycles, which helps to delay the capacity decay of the material. The current response within the potential variation range is relatively stable, especially in the high-voltage section. The higher current response indicates that the antimony-doped NCM90 has good rate performance under fast charge and discharge conditions. This is because antimony doping improves the structural integrity of the material, so that it can still maintain good electrochemical stability at higher current densities. In the first cycle, the CV curve shows a slight irreversible feature, which is related to the initial activation process of the material. However, compared with traditional NCM materials, the stability of the interface layer after antimony doping is improved, which can effectively weaken the decomposition of the electrolyte on the electrode surface, thereby slowing down the thickening of the SEI layer during long cycles.
[0066] The battery prepared with the Sb-NCM90 positive electrode material obtained in Example 1 was subjected to a long cycle performance test. The test results are as follows: Figure 4 As shown, through Figure 4It can be found that the charge-discharge efficiency is always maintained at about 99% within 1 to 100 charge-discharge cycles. The discharge capacity of Sb-NCM90 increases from the initial 244 mAh g -1 Down to 221mAh g -1 Compared with NCM90, which dropped to 39% (under the same test conditions), the charge-discharge specific capacity retention rate was greatly improved, proving the importance and feasibility of this positive electrode material.
[0067] The battery prepared with the Sb-NCM90 positive electrode material obtained in Example 1 was subjected to EIS test after being left to stand for one day. The test results are as follows: Figure 5 As shown. Figure 5 It can be seen that the impedance changes with frequency: From the test results, it can be seen that the impedance value of the positive electrode material shows a trend of first rising and then falling with the change of frequency. In the low-frequency region, the impedance value is high; as the frequency increases, the impedance value gradually rises to a peak value; then, in the high-frequency region, the impedance value gradually decreases. In the low-frequency region, the higher impedance value may indicate that the material has a larger electrochemical impedance at this frequency, and a larger voltage drop will be generated when the current passes through. This may be related to the internal structure, electrochemical properties or surface state of the material. High-frequency region characteristics: In the high-frequency region, the decrease in the impedance value may mean that the material exhibits a smaller electrochemical impedance at this frequency, and the voltage drop generated when the current passes through is smaller. This may be because high-frequency current can penetrate the material more effectively, reducing the influence of electrochemical impedance. The position where the impedance value reaches the peak may reflect a certain specific electrochemical behavior or structural characteristics of the material. This peak point may be the critical point for the transformation of the electrochemical behavior of the material at different frequencies, which is of great significance for understanding the electrochemical properties of the material.
[0068] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0069] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A Sb-NCM positive electrode material, characterized in that: The chemical formula of the Sb-NCM cathode material is Li[Ni x Mn y Co z Sb t ]O2, where x≥0.8, y≤0.1, z≤0.1, t≤0.1 and y+z+t≤0.
2.
2. A Sb-NCM positive electrode material according to claim 1, characterized in that: The chemical formula of the Sb-NCM cathode material is Li[Ni 0.895 Mn 0.05 Co 0.05 Sb 0.005 ]O2.
3. The method for preparing a Sb-NCM positive electrode material according to any one of claims 1 to 2, characterized in that: The steps include: 1) dissolving nickel salt, manganese salt and cobalt salt to obtain a mixed solution, mixing the mixed solution with an alkaline solution to react and obtain a hydroxide precipitate; 2) Preliminarily calcining the hydroxide precipitate obtained in step 1) to obtain an intermediate product; 3) The intermediate product is mixed with a lithium source and an antimony source, and calcined again to obtain a Sb-NCM positive electrode material; The molar ratio of nickel salt, manganese salt, cobalt salt and antimony source is x+t:y:z:t.
4. The method for preparing a Sb-NCM positive electrode material according to claim 3, characterized in that: The reaction temperature in step 1) is 35-40° C., the reaction time is 0.5-2 h, and the reaction pH is 8.5-9.
5.
5. The method for preparing a Sb-NCM positive electrode material according to claim 3 or 4, characterized in that: The nickel salt includes one or more of nickel nitrate, nickel chloride and nickel sulfate; The manganese salt includes one or more of manganese nitrate, manganese chloride and manganese sulfate; The cobalt salt includes one or more of cobalt nitrate, cobalt chloride and cobalt sulfate.
6. The method for preparing a Sb-NCM positive electrode material according to claim 5, characterized in that: The reaction in step 1) is carried out under ultrasonic conditions, and the frequency of the ultrasound is 20-100 kHz.
7. The method for preparing a Sb-NCM positive electrode material according to claim 6, characterized in that: The temperature of the preliminary calcination in step 2) is 300-500° C., and the time of the preliminary calcination is 60-120 min.
8. A method for preparing a Sb-NCM positive electrode material according to claim 6 or 7, characterized in that: The re-calcination in step 3) includes a first stage calcination and a second stage calcination performed sequentially; The calcination temperature of the first stage is 450~570℃, and the calcination time is 200~300min; The calcination temperature of the second stage is 750~870℃, and the calcination time is 1000~1400min; The calcination atmospheres of the first stage calcination and the second stage calcination are independently oxygen atmospheres.
9. The method for preparing a Sb-NCM positive electrode material according to claim 8, characterized in that: The lithium source in step 3) includes one or more of lithium carbonate, lithium hydroxide, lithium sulfate and lithium nitrate; The antimony source includes antimony pentoxide and / or sodium antimonate.
Citation Information
Patent Citations
Method for preparing lithium nickel cobalt aluminum oxides serving as lithium ion battery positive electrode material
CN102173465A
Preparation method for manganese solid solution anode material of lithium ion battery material
CN103606667A
Lithium-rich manganese-based precursor, preparation method thereof and lithium-rich manganese-based positive electrode material
CN109704415A
Positive electrode active material, positive electrode plate and lithium ion secondary battery
CN112447964A
Cobalt gradient high-nickel ternary positive electrode material, preparation method thereof and lithium ion battery
CN115259244A